2019
DOI: 10.3390/ijms21010012
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Differentiation Characteristics of Endothelium Determine Its Ability to Form Pseudo-Embryos in Tomato Ovules

Abstract: The endothelium is an additional cell layer, differentiating from the inner epidermis of the ovule integument. In tomato (Solanum lycopersicum L.), after fertilization, the endothelium separates from integument and becomes an independent tissue developing next to the growing embryo sac. In the absence of fertilization, the endothelium may proliferate and form pseudo-embryo. However, the course of the reorganization of endothelium into pseudo-embryo in tomato ovules is poorly understood. We aimed to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Those data affirm that the different endothelial qualifications such as ECD and hexagonality reach the evaluation dimensions consistency which coincide with Joo et al's publications [23]. The size and hexagon of endothelial cell area can be the unique property for the human develop-ment [24]. Meanwhile, Radman et al's literatures have reported that the sharp of the human endothelial be associated with the age growth stage, even that so-called childhood obesity criterion can be realized fiercely different with adolescence and earlier adulthood [25].…”
Section: The Characteristic Of 4-30 Years Chinese's Endothelialsupporting
confidence: 87%
“…Those data affirm that the different endothelial qualifications such as ECD and hexagonality reach the evaluation dimensions consistency which coincide with Joo et al's publications [23]. The size and hexagon of endothelial cell area can be the unique property for the human develop-ment [24]. Meanwhile, Radman et al's literatures have reported that the sharp of the human endothelial be associated with the age growth stage, even that so-called childhood obesity criterion can be realized fiercely different with adolescence and earlier adulthood [25].…”
Section: The Characteristic Of 4-30 Years Chinese's Endothelialsupporting
confidence: 87%
“…The endothelium in the tomato ovule is the internal epidermis of integument, transformed into an independent tissue. In the early stages of embryo development, the endothelium separates and protects the developing endosperm from dying integumental parenchyma cells due to PCD [18]. Tapetal cells in anthers during pollen formation completely degenerates, while the endothelium in tomato ovules remains practically until the seed fully matures.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, apparently, due to the hormonal deviations in cells around the embryo sac, so-called pseudo-embryonic tissue is formed in the unfertilized ovules from the inner epidermis of the integument. In turn, it stimulates the ovary to develop and form parthenocarpic fruits [18].The aim of this work was to identify the cytoembryological features of anthers and pollen development to establish morphological factors for pollen sterility at key stages of the androecium and gynoecium development in transgenic tomato plants with anomalies of generative organs, as well as in transgenic tomatoes without visible phenotypic anomalies, but with partially sterile pollen. These model tomato plants were previously used to study pseudo-embryo formation in the ovules of parthenocarpic fruits [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous research, a detailed electron microscopic study of the ovule histogenesis in normal and genetically transformed tomatoes was carried out to reveal the cytoembryological causes of the endothelium growth and its transformation into pseudo-embryonic tissue in the ovules of transgenic tomatoes [11]. It was revealed that the mechanism of the detachment process of the inner epidermis from integument is the programmed death of adjacent parenchyma cells of the integument itself [11]. Ricinosomes, which are the markers of PCD, were found in these cells [12].…”
Section: Introductionmentioning
confidence: 99%